Histograms in Breast Density Classification: Are 4 Better Than 1? - Izzati Muhimmah; Erika RE Denton; Reyer Zwiggelaar (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2005)
Breast density is known to be an important indicator of breast cancer risk. Quantitative estimationapproaches have been developed and some of these are based on grey level or texture metrics. Developing anexample of the former, we combined multi-resolution histograms and pattern matching approaches. The resultsshow good agreement compared to expert radiologist classification. The presented approach provides similarresults to existing methods and limitations are discussed.Keywords: multi-resolution histogram technique, mammography, breast density classification